Life and Death in Besieged Leningrad, 1941-1944
XXVII, 243 p.
Keywords: From 1941-1944 Leningrad saw by far the largest-scale famine ever to occur in a developed society. This book examines the nature and consequences of the extreme conditions created by the German blockade of Leningrad between September 1941 and January 1944. Using declassified documents from Party and State archives in Moscow and St Petersburg and interviews with survivors, the authors have produced the most informed and detailed analysis to date of the impact of the siege on the lives and health of the people of Leningrad.